Virtual Reality Check. - WARNER, NICHOLAS (Art Monthly, 2013)
The article focuses on internet art and its potential representation in a gallery setting. The article discusses the difference between experiencing net art as it as made to be experienced online and in a physical gallery, the net art movement's relation to Fluxus and the Mail Art network as counter-cultures and the lack of accessibility to net art. The article also discuss net art as a separate and parallel discourse to contemporary art.